Improving Savings, Health, and Happiness by Modifying How the Family Operates the Home - Randall A. Cantrell (EDIS)
Does your home routine need a tune-up? This 3-page fact sheet discusses ways to improve your home’s family operations, which are routines and behaviors practiced at home by your family. Written by Randall A. Cantrell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.